2011
DOI: 10.4103/0378-6323.77486
|View full text |Cite
|
Sign up to set email alerts
|

Palmar cutaneous metastasis from carcinoma cervix

Abstract: Carcinoma of the uterine cervix is the most common gynecological malignancy in developing countries. However, its cutaneous metastasis is a rare entity. The reported incidence of cutaneous metastasis ranges from 0.1 to 2%. Frequent sites of cutaneous metastasis in decreasing order are: abdominal wall, vulva and anterior chest wall. To the best of our knowledge, only three cases of cutaneous metastasis to the upper extremity have been reported in the world. We report a case of a 74-year-old postmenopausal lady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This case, however, is distinctive for several reasons. First, in prior reports of cutaneous metastases from cervical squamous cell carcinoma, the grossly visible nodules are usually single or a small cluster of multiple papules [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In our patient's case, the cutaneous metastases were innumerable and located diffusely over the anterior abdominal wall, vulva, perineum, and bilateral proximal lower extremities (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case, however, is distinctive for several reasons. First, in prior reports of cutaneous metastases from cervical squamous cell carcinoma, the grossly visible nodules are usually single or a small cluster of multiple papules [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . In our patient's case, the cutaneous metastases were innumerable and located diffusely over the anterior abdominal wall, vulva, perineum, and bilateral proximal lower extremities (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This clinical scenario is even less common in literature originating from the United States, due to the lower overall incidence of cervical cancer [3][4][5] . Case reports have documented various sites of cutaneous metastases, including the face and neck [6] , scalp [7][8][9] , vulva [5,[10][11] , upper and lower extremities [12][13] , umbilicus (Sister Mary Joseph nodule) [14] , trunk/abdominal wall [3][4][5]15] , and surgical incision/drain sites [16][17] . Prior authors have found that the occurrence of metastases to the skin generally implies terminal disease, with the average survival following diagnosis ranging from 3-6 months, even in cases where palliative chemo-and radiotherapy are administered [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous metastasis in the palmar area from visceral cancer has been reported in only four cases in the English-language literature13-16 since Camiel et al originally reported skin metastasis on palm and sole from lung cancer. However, this had not yet been reported in the Korean-language literature.…”
Section: Discussionmentioning
confidence: 99%